#BoikotScarlett Cancel Culture Movement - Virginia Meiske Ardiningrum; Jefri Audi Wempi Liwoso (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Crisis management is an important aspect in Public Relations (PR) practice, especially in the digital era when public perception can change rapidly due to the dynamics of social media. One phenomenon that often causes a reputation crisis for companies is cancel culture, a collective movement that rejects individuals or brands that are considered to be in conflict with certain social values. This phenomenon is increasingly widespread, one of which is affecting a local beauty company, Scarlett Whitening. The cancel culture movement #BoikotScarlett emerged due to a video uploaded by Scarlett Whitening's CEO on Instagram that was considered to be siding with Israel in the midst of the Israel-Palestine conflict. This sparked public criticism and calls for a boycott that spread widely on social media, thus impacting the brand's reputation and decreasing consumer interest. This study aims to analyze how Scarlett Whitening's crisis management is carried out in dealing with cancel culture, as well as the factors that encourage people's involvement in this movement. The theory used is the New Social Movement theory which explains how social groups gather and act to resolve issues that are considered important. The research method used is qualitative with a constructivism paradigm, and data collection techniques through interviews and literature studies. The results of the study show that the cancel culture #BoikotScarlett is a real example of how social media can mobilize public opinion and change a brand's image in a short time. Although Scarlett Whitening has made clarifications and crisis communication strategies, the response is considered less firm, making the boycott movement still continue. This study emphasizes that companies need to implement more effective and careful issue management strategies in their corporate communication practices to avoid the negative impacts of cancel culture and maintaining brand reputation. The results of the study show that most consumers who stopped using Scarlett products have various reasons, including perceptions of product quality that are considered mediocre and brand involvement in controversial issues that trigger dissatisfaction. Triangulation analysis shows that consumers expect rebranding and more transparency from Scarlett Whitening in dealing with circulating issues. Key recommendations for the brand include improving product quality, more effective communication strategies in dealing with crises, and more transparent policies on social issues that concern consumers. Thus, this study provides insights for companies in managing reputation and maintaining customer trust in the digital era."